Visual Acuity alterations in heavily impaired Congenital Zika Syndrome (CZS) children - Baran, Luiz C. P.; Lima, Diego da S.; Silva, Leonardo A.; Tabares, Heydi S.; Dias, Sarah L.; Zin, Andrea Araújo; Moreira, Maria E. L.; da Costa, Marcelo F.; Ventura, Dora F. (Frontiers in Ophthalmology, 2022)
Introduction This study aimed to assess visual acuity (VA) in Congenital Zika Syndrome (CZS)-children to evaluate visual loss. To that end we evaluated 41 CZS - children, from Rio de Janeiro using Teller Acuity Cards. Methods To asses VA, we evaluated 41 CZS - children, from Rio de Janeiro using Teller Acuity Cards. The children had Zika virus-infection confirmed by reverse transcription–polymerase chain reaction (RT-PCR) or clinical evaluation. Results In 39 out of 41 (95%) children, the VA scores were below normative values, while in 10 cases, VA was only marginally below normal; in the remaining 29 cases, VA was more than 0.15 logMAR below the lower limit. There was no correlation between VA and the cognitive domain tasks, although there was a correlation between VA and motor domain tasks. Thirty-seven children performed at least one task in the cognitive set, while fourteen children did not perform any task in the motor set. Children with VA above the lower limit performed better in the cognitive and motor tasks. Discussion We concluded that ZIKV- infected children with CZS were highly VA impaired which correlated with motor performance, but not with cognitive performance. Part of the children had VA within the normal limits and displayed better performance in the cognitive and motor sets. Therefore, even if heavily impaired, most children had some degree of VA and visual function.